How the lack of english didactics and teaching practice oriented to children affects graduates’ performance when teaching students from 6 to 12 years old. Case: graduates from the Licenciatura en Idioma Inglés Opción Enseñanza from the Foreign Language Department of the University of El Salvador. - Candelario Chávez, Beatriz Azucena; González Quintanilla, Sara Elizabeth; Gutiérrez Pastul, Walter Omar (2024)
This report synthesizes the main findings of this research, including the results of a teacher’s questionnaire, kids and teachers’ checklist through graphics which represent and explain the results gathered during the whole investigation. The research was carried out during a children course. The course lasted 8 Saturdays. Researchers observed the classes of graduates from the University of El Salvador at Pro-Lingua Institute in a period of four Saturdays. The reason of this observation was to gather the information from the kids and teachers checklists. Besides, a questionnaire was given to the teachers in order to give answers according to their own professional knowledge and experience. Also, teachers were held to an interview, which was recorded, to identify difficulties they have had due to the lack of methodology given in Licenciatura en Idioma Inglés Opción Enseñanza from the Foreign Language Department of the University of El Salvador.